2017
DOI: 10.12693/aphyspola.131.1319
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Study of the Microstructure and Phase Composition of Nanoausferritic Ductile Iron Alloy Using SEM, TEM, Magnetometer, and X-Ray Diffraction Methods

Abstract: In this paper the microstructure and phase composition of ausferritic ductile iron alloy were investigated by scanning electron microscopy, transmission electron microscopy and X-ray diffraction methods. In order to obtain the nanoausferritic microstructure in the alloy, the austempering heat treatment was performed at relatively low temperature. As a result, a specific kind of microstructure, containing nanocrystalline ausferrite and retained austenite blocks, was obtained in each heat-treated sample. The vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is because the finer grains of ausferrite are obtained by nucleation and growth. In the present case, the large super-cooling at a lower temperature (260°C) facilitates more nuclei formation and/or partial transformation, after which the austempering at a higher temperature (400°C), ensures the growth and completion of the transformation [32]. Thus, boundary strengthening and phase hardening (ausferrite) are the operational micro-mechanisms that are responsible for the improved hardness.…”
Section: Mechanical Properties Of the As-cast And Austempered Alloys Producedmentioning
confidence: 75%
See 1 more Smart Citation
“…This is because the finer grains of ausferrite are obtained by nucleation and growth. In the present case, the large super-cooling at a lower temperature (260°C) facilitates more nuclei formation and/or partial transformation, after which the austempering at a higher temperature (400°C), ensures the growth and completion of the transformation [32]. Thus, boundary strengthening and phase hardening (ausferrite) are the operational micro-mechanisms that are responsible for the improved hardness.…”
Section: Mechanical Properties Of the As-cast And Austempered Alloys Producedmentioning
confidence: 75%
“…The inhomogeneity that characterized the ausferrite morphology may be due to the micro-segregation effect in the ferrite and retained austenite comprising the ausferrite. It could also be due to an incomplete reaction in the entire austenite which remains untransformed in the microstructure [31][32][33]. For most of the compositions, the results of the image analysis used to estimate the volume fractions of the phases revealed that the single step austempering process yielded slightly higher ausferrite content compared with the two step austempering process.…”
Section: No /mentioning
confidence: 99%
“…It has also been found that the new material based on bentonite-modified polyethylene wax reduces casting shrinkage and slightly increases viscosity, which is therefore excellent for lost-wax casting. After the casting process, quality control is essential, especially when new casting methods [18][19][20][21] or new materials are introduced, such as in the case of casting patterns made of composites based on polyethylene-ceramic waxes. Destructive and non-destructive research techniques are used to analyse the surface quality of castings, internal defects, shape or continuity of the structure.…”
Section: Introductionmentioning
confidence: 99%

Archives of Foundry Engineering

Czarnecka-Komorowska,
Gawdzińska,
Popielarski
2022